Thrombocytopenia in primary antiphospholipid syndrome: association with prognosis and clinical implications. (10th May 2022) - Shi, Yu; Zhao, Jiuliang; Jiang, Hui; Huang, Can; Qi, Wanting; Song, Yijun; Wang, Qian; Li, Mengtao; Tian, Xinping; Zhao, Yongqiang; Zeng, Xiaofeng
Abstract: Objectives: Thrombocytopenia, a frequent clinical manifestation in patients with APS, could be an independent predictor of recurrent thrombotic, obstetric and severe extracriteria events. Methods: This single-centre prospective study enrolled 218 consecutive patients diagnosed with primary APS between 2010 and 2021. Thrombocytopenia was defined as a platelet count less than 100 × 10 9 /L. Results: Our cohort included 74 (33.94%) patients with thrombocytopenia and 144 patients with a continuous normal platelet count. Comparison of baseline characteristics indicated that patients with thrombocytopenia had more visceral venous thromboses [10 (13.51%) vs 5(3.47%); P = 0.009] and extracriteria manifestations [mainly haemolytic anaemia; 20 (27.03%) vs 17 (11.81%); P = 0.007]. Hypocomplementemia was more likely among patients with thrombocytopenia [19 (25.68%) vs 16 (11.11%); P = 0.01]. The presence of aCL-IgG/IgM, anti-β2-glycoprotein I and lupus anticoagulant were more frequently detected in patients with thrombocytopenia. In survival analysis, thrombotic, obstetric and severe extracriteria survival rates were significantly worse in patients with thrombocytopenia. In multivariate Cox regression, thrombocytopenia was an independent risk factor for all endpoint events, including thrombotic events [hazard ratio (HR) 2.93 (95% CI 1.31, 6.56), P = 0.009], pregnancy morbidity [HR 8.00 (95% CI 2.43, 26.37), P = 0.0006] and severe extracriteria events [HR 15.27 (95% CI 1.85, 125.98), P = 0.01]. Conclusion: Thrombocytopenia could identify primary APS patients at high risk of developing thrombotic events, pregnancy morbidity and severe extracriteria events.